2018
DOI: 10.1542/peds.2017-2934
|View full text |Cite
|
Sign up to set email alerts
|

Length of Stay and Cost of Pediatric Readmissions

Abstract: Readmitted children spend twice as many days in the hospital compared with children who are not readmitted and have higher hospital costs, especially when readmitted to a different hospital. In addition to readmission rate, readmission metrics may benefit from measurement of total LOS and costs for both the index admission and its associated readmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
23
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 18 publications
5
23
1
3
Order By: Relevance
“…Because the user does not have access to patient records or clinical outcomes, there is no way to formally validate the information extracted with actual patient data. Nonetheless, the NRD has been extensively employed throughout the literature as a tool for exploring readmission trends across a wide range of subspecialties 4549 .…”
Section: Discussionmentioning
confidence: 99%
“…Because the user does not have access to patient records or clinical outcomes, there is no way to formally validate the information extracted with actual patient data. Nonetheless, the NRD has been extensively employed throughout the literature as a tool for exploring readmission trends across a wide range of subspecialties 4549 .…”
Section: Discussionmentioning
confidence: 99%
“…28,29 Although data regarding total Medicaid expenditures on pediatric readmissions are not readily available, readmissions for Medicaid beneficiaries cost ∼$1000 more on average than those for privately insured patients, and episodes of care that result in readmissions are 2.3 times more expensive than those without readmissions. 13,30 There are several potential explanations for the higher readmission rates observed in Medicaid-insured patients who may shed light on strategies for eliminating this disparity. Consistent with previous studies, we found that patients insured by Medicaid had more chronic or complex conditions than those insured by private insurers.…”
Section: Figurementioning
confidence: 99%
“…The definition of rehospitalization varies across studies. The most commonly used definition of rehospitalization is rehospitalization between 28 and 31 days after discharge for unplanned reasons (4)(5)(6)(7)(8). Rehospitalization rates for children aged 0-18 years range from 3.4-28.6% (5,(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%